Time to rethink the management intensity in a Mediterranean oak woodland: the response of insectivorous birds and leaf-chewing defoliators as key groups in the forest ecosystem - Pereira, Pedro (2015)
Context The Iberian cork oak Quercus suber montados are dynamic agro-silvo-pastoral systems, contrasting with the abandonment trend of other Mediterranean forested areas. • Aims We aimed to identify the effect of management type and vegetation features on breeding insectivorous birds and leaf-chewing defoliator insects. • Methods In central Portugal, we selected two groups of 20 sites: dense montados (DM, high cover of cork oaks and low cattle impact) and sparse montados (SM, low cover of oaks and high cattle impact). We collected variables associated with vegetation features, bird community and chewing defoliators. • Results The two systems differed significantly in oak trunk diameter, oak and shrub cover, tree and shrub diversity. Ground bird densities were higher in SM with fragmented shrub cover. In DM, higher woody vegetation cover and diversity can promote shrub birds and leaf warblers. Oak defoliation was mainly attributed to the sawfly Periclista andrei. Sawfly defoliation was significantly higher in SM and negatively correlated with shrub cover. • Conclusions Our results highlight (1) the relevance of management activities conducted at the shrubby layer, (2) the need of an increase in tree diversity and density and (3) the maintenance of a mosaic landscape in order to improve the bird community richness and reduce the defoliation impact in montado system.